Real-world trends in rheumatic disease rates among pregnancies in Ontario, Canada: A repeated cross-sectional study - Shenthuraan Tharmarajah; Zain Abideen; Swaleh Hussain; Sara J.T. Guilcher; Lisa M. McCarthy; Dharini Mahendira; Howard Berger; Mina Tadrous (PLoS ONE, 2025)
Objective Despite increasing rheumatic disease prevalence among female individuals in Ontario, Canada, research is limited on whether this has translated to an increased proportion of pregnancies with rheumatic diseases. This study aimed to assess rheumatic disease rates among pregnant individuals in Ontario, Canada. Methods Using healthcare administrative claims databases from ICES, the proportion of pregnancies with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) from April 2011 to March 2021 were examined. The Mann-Kendall rank correlation test was used to test for trends in overall and individual rheumatic disease rates across the study period. Results In total, 1,408,100 pregnancies were recorded from fiscal years 2011–2020 in Ontario. Of these, 4,392 involved patients with rheumatic diseases. The overall rheumatic disease rate among pregnant individuals increased by 24% from 28.3 to 35.2 pregnancies per 10,000 over the study period (p = 0.0157). RA rates increased 22% from 11.1 to 13.5 per 10,000 (p = 0.0056), while PsA rates increased 111% from 0.9 to 1.9 per 10,000 (p = 0.0157). SLE, AS, and multiple rheumatic disease rates did not increase significantly. Conclusion The proportion of individuals with rheumatic diseases pursuing pregnancy in Ontario has increased, perhaps aided by advancements in disease diagnostics and treatment strategies. Further research is needed to link antirheumatic drug safety to pregnancy outcomes and explore other factors that may influence pregnancy rates among this patient population.